New Mycobacterium tuberculosis Complex Sublineage, Brazzaville, Congo - Sven Malm; Laure S. Ghoma Linguissi; Emmanuel M. Tekwu; Jeannhey C. Vouvoungui; Thomas A. Kohl; Patrick Beckert; Anissa Sidibe; Sabine Rüsch-Gerdes; Igor K. Madzou-Laboum; Sylvie Kwedi; Véronique Penlap Beng; Matthias Frank; et al. (Emerging Infectious Diseases, 2017)
Tuberculosis is a leading cause of illness and death in Congo. No data are available about the population structure and transmission dynamics of the Mycobacterium tuberculosis complex strains prevalent in this central Africa country. On the basis of single-nucleotide polymorphisms detected by whole-genome sequencing, we phylogenetically characterized 74 MTBC isolates from Brazzaville, the capital of Congo. The diversity of the study population was high; most strains belonged to the Euro-American lineage, which split into Latin American Mediterranean, Uganda I, Uganda II, Haarlem, X type, and a new dominant sublineage named Congo type (n = 26). Thirty strains were grouped in 5 clusters (each within 12 single-nucleotide polymorphisms), from which 23 belonged to the Congo type. High cluster rates and low genomic diversity indicate recent emergence and transmission of the Congo type, a new Euro-American sublineage of MTBC.